Winning by process the state and neutralization of ethnic minorities in Myanmar - Bertrand, Jacques 1965-; Pelletier, Alexandre; Thawnghmung, Ardeth Maung (Southeast Asia Program Publications, an imprint of Cornell University Press, 2022)
Winning By Process : Leveraging Formal Negotiation, State Institutions and War -- The Failure to Win by War : The Limits of Bamar Dominance and Ethnic Minority Repression -- Democratization : Layering and Sequencing in the State Institutional Arena -- Process over War : From Ceasefire to Political Dialogue -- Normalizing Weak Ethnic States : Constitutional Lock-In and Implementing Layers -- Outflanking and the Erosion of de Facto Autonomy -- Fragmentation, Marginalization, and Subjugation : Layering and Locking-In Ethnic Recognition
Includes bibliographical references and index
Keywords: Minorities / Government policy / Burma; Minorities / Political aspects / Burma; Ethnic conflict / Burma; Ethnic conflict; Ethnic relations; Political aspects; Minorities; Government policy; Minorities; Political aspects; Burma / Politics and government / 21st century; Burma / Ethnic relations / Political aspects; Burma